The Use of Chunking Strategy in Teaching Reading Comprehension - Samhudi (Medan Resource Center, 2022)
This research was aimed to find out whether using chunking strategy was effective in teaching reading comprehension. In this case, the researcher used quantitative data approach by using experimental design. There were two classes at ninth grade of SMPN 1 Nisam North Aceh as the sample of this research. There were class IX/3 as experimental consist of 24 students and IX/2 as control group consist of 22 students. In experimental group, the researcher used chunking strategy in teaching reading comprehension. After teaching learning process for three meetings, the researcher gave post-test. The result was shown that the students’ achievement in experimental group was higher than control group. It was proved by the average score from pre-test of experimental group was 66,8 and control group was 64,5. Furthermore, the result of post-test of experimental group was 83,2 and control group was 70,3. It could be concluded that using chunking strategy was effective in teaching reading comprehension.